Association between frailty and the combination of physical activity level and sedentary behavior in older adults - Venicius Dantas da Silva; Sheilla Tribess; Joilson Meneguci; Jeffer Eidi Sasaki; Cíntia Aparecida Garcia-Meneguci; José Ailton Oliveira Carneiro; Jair Sindra Virtuoso (BMC, 2019)
Abstract Background The combined association of physical activity and sedentary behavior with adverse health factors is not yet clear in the literature. A combined analysis of physical activity level and sedentary behavior may provide evidence of the interrelation between these behavioral variables and the frailty syndrome. Thus, the aim of this study was to examine the relationship between physical activity level, sedentary behavior and frailty in older adults. Methods In this study, we evaluated 457 older adults (age range = 60 to 96 years old) from the Longitudinal Study of the Elderly Health of Alcobaça, Bahia. The frailty condition was defined by the presence of three or more of the following criteria: unintentional weight loss, slow walking speed measured over a 4.57 m test, a reduction of manual grip strength and exhaustion. Based upon these criteria, participants were classified as non-frail or frail. Physical activity level and time spent in sedentary behavior were assessed with the International Questionnaire of Physical Activity. Descriptive statistics were used to characterize the sample. To examine the combined association of physical activity and sedentary behavior with frailty, chi-square and Poisson regression tests were used. Statistical significance was defined as p ≤ 0.05. Results The prevalence of frailty was 8.8% (n = 40), with higher prevalence observed with increasing age. Low physical activity level combined with excessive time spent in sedentary behavior (physical activity level < 150 min/wk. and sedentary behavior ≥540 min/day) was associated with frailty, resulting in a prevalence ratio of 2.83 (95% CI, 1.23 to 6.52). Conclusion Frailty is more prevalent among older adults who exhibit insufficient levels of physical activity combined with a great amount of time spent in sedentary behavior, even when adjusted for sociodemographic factors.